(untitled) (Indian Journal of Animal Production and Management, 2014)
Traditionally, male piglets are surgically castrated from a very early age to eliminate a number of undesirable characteristics, including aggressive behaviour and the presence of “boar taint.” This surgical castration is often carried out within the first week of life, as several countries have laws that permit castration at this age without the use of anaesthesia or analgesia. This practice has considerable welfare implications for the piglets, and the increase in public interest in the welfare of farmed animals has many producers looking for alternatives. A large representative of interested parties within the European Union (EU) pork industry have produced a declaration for the voluntary phase-out of all surgical castration in pigs by January 1st, 2018. To accomplish this, alternative methods to surgical castration must be researched and employed on a regular basis. This review will discuss the alternatives that are currently available as well as those that are under development.